(untitled) (EU and comparative law issues and challenges series (ECLIC), 2023)
The emergence of internet technologies and social media platforms has affected all aspects of life, especially among younger generations. In this new media world of social media, for stakeholders dealing with the 15–24-year-old population it is important to understand how to communicate and engage with them. Using a combination of qualitative/quantitative research methodology, this paper aims to provide a comprehensive, descriptive view of the values, perception, and behaviour of youth (15–24) in Croatia when it comes to digital media channels and especially social media. Research results confirmed that social networks, messaging services and browsing internet are the dominant activities of young generation. YouTube, Instagram, and Facebook are the most popular social network, and principals in content creation are authenticity, customization, and interactivity. These results should serve as a basis for communication strategies within this target audience. And since the way young use social networks and create/consume content changes daily, legal framework should follow.